Efektivitas Pengawasan Internal dan Eksternal dalam Pencegahan Korupsi di PT Pertamina (Persero): Tinjauan Hukum Administrasi Negara - Hasudungan, Oktar; Asri, Ardison (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Corruption within PT Pertamina (Persero) remains a critical issue that not only causes significant state financial losses but also undermines public trust. This study aims to evaluate the effectiveness of internal and external supervisory mechanisms in preventing corruption within the company, viewed from the perspective of State Administrative Law. Employing a qualitative descriptive approach and a case study design, the research analyzes the roles and functions of various oversight institutions, including Pertamina’s internal audit division, the Supreme Audit Agency (BPK), the Corruption Eradication Commission (KPK), and other relevant legal authorities. The findings indicate that although supervision mechanisms are formally established, their implementation still faces several challenges. These include regulatory gaps, limited inter-agency coordination, and weaknesses in corporate governance. The ineffectiveness of oversight functions contributes to vulnerabilities in the company’s anti-corruption framework. Therefore, the study recommends the strengthening of regulatory frameworks, enhancement of transparency, and optimization of synergy between internal and external oversight bodies. These reforms are deemed essential to build a more accountable and corruption-resistant governance system in state-owned enterprises, particularly in strategic sectors such as energy. The research findings have practical implications for policymakers and supervisory institutions in improving public sector integrity through better administrative oversight.